The Effect of Methanol Concentrations Against Phenolic Total Content and Antioxidant of Balakacida Leaves (Chromolaena odorata) - Sriwijayanti Sriwijayanti; Ahmad Firdaus; Boima Situmeang; Holisha Widiyanto; Dian Susvira (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
The balakacida plant with the Latin name Chromolaena odorata is a plant that lives in a tropical climate. The balakacida plant is a plant of the Asteraceae Family. Phytochemical tests on balakacida leaves showed the presence of secondary metabolites of the tannin, phenol, flavonoid, saponin and steroid groups. This study aims to extract balakacida leaves and test the total phenolic and antioxidant content. Sample extraction was carried out by the maceration method using methanol solvent. Testing of total phenolic content using the Folin Ciocalteu method, while testing of antioxidant content using the DPPH method using a UV-Vis spectrophotometer. The results showed that the concentration of methanol solvent significantly affected the acquisition of total phenolics and antioxidants. The highest total phenolic content was obtained at a methanol extract concentration of 80% of 145.64 mg GAE/g. For antioxidant content, a methanol extract concentration of 60% showed the highest activity with an average DPPH % inhibition of 59.77%. It can be concluded that a methanol extract concentration of 60% is the optimal concentration to produce balakacida leaf extract with the best antioxidant activity, although not with the highest total phenolic content.